Systematic review of success factors and barriers for software process improvement in global software development. Issue 5 (1st October 2016) - Khan, Arif Ali; Keung, Jacky
Abstract : Nowadays, many software development organisations are globalising their work throughout the world. The motivation behind the software globalisation is competitive advantage and business profits that it yields to an organisation. Besides, these organisations are facing various challenges due to the distributed nature of the software development. However, software process improvement (SPI) is one of the biggest issues in the domain of global software development (GSD). The aim of this research study is to identify success factors and barriers to assist GSD organisations for successful implementation of SPI program. Accordingly, a systematic literature review approach was adopted to identify the success factors and barriers. A total of nine success factors and six barriers were identified that could impact SPI. Using the criteria of the factors having a frequency >50% as critical, total four success factors were ranked as critical success factors, i.e. management commitment, staff involvement, allocated resources and pilot projects. Moreover, total four barriers were classified as critical barriers, i.e. lack of resources, inexperienced staff, organisational politics and time pressure.